2017
DOI: 10.1021/jacs.6b10781
|View full text |Cite
|
Sign up to set email alerts
|

On the Oxidation State of Manganese Ions in Li-Ion Battery Electrolyte Solutions

Abstract: We demonstrate herein that Mn and not Mn, as commonly accepted, is the dominant dissolved manganese cation in LiPF-based electrolyte solutions of Li-ion batteries with lithium manganate spinel positive and graphite negative electrodes chemistry. The Mn fractions in solution, derived from a combined analysis of electron paramagnetic resonance and inductively coupled plasma spectroscopy data, are ∼80% for either fully discharged (3.0 V hold) or fully charged (4.2 V hold) cells, and ∼60% for galvanostatically cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 31 publications
3
111
1
Order By: Relevance
“…Furthermore, the dissolution of Mn 2+ was accelerated at elevated temperatures due to the decomposition of the electrolyte. The absence of Mn 3+ is contrary to those studies, which reported dissolution of Mn 2+ and Mn 3+ from LMO or LNMO cathode materials into LIB electrolytes [38, 39].…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, the dissolution of Mn 2+ was accelerated at elevated temperatures due to the decomposition of the electrolyte. The absence of Mn 3+ is contrary to those studies, which reported dissolution of Mn 2+ and Mn 3+ from LMO or LNMO cathode materials into LIB electrolytes [38, 39].…”
Section: Discussioncontrasting
confidence: 84%
“…Nevertheless, several studies report on dissolved Mn 3+ being the main manganese species in common electrolyte in case of the LMO cathode, with abundances of 67–78% after storage and 60–80% after electrochemically treatment in LMO||Graphite cells. For LNMO, the Mn 3+ amount in the electrolyte after storage was reported to be 12–44% of total dissolved manganese [38, 39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is consistent with the involvement of some Mn atoms in a disproportionation reaction, as has been proposed in other Li-ion systems. [47][48][49] However, the total lateral deviation is fairly minimal and the spectra are dominated by the +4 oxidation in all cases. Therefore, the risingedge behavior may be due to subtler effects, including smaller changes in covalency.…”
Section: Resultsmentioning
confidence: 99%
“…[12,13,47,[49][50][51][52] During storage in the air, O 2 /H 2 O/CO 2 could also react with these partially coordinated metal cations and so surface reconstruction occurs, leading to species like LiOH, Li 2 CO 3 , and LiHCO 3 at the surface. For example, surface reconstruction occurs commonly in electrodes upon exposure to the electrolyte and/or during electrochemical cycling, as in recent studies, and is attributed to the reaction between organic molecules in the electrolyte and partially coordinated metal cations in MO 6 octahedra at the particle surface.…”
mentioning
confidence: 99%